Strangers and scapegoats : extending God's welcome to those on the margins - Vos, Matthew (Baker Academic; Grand Rapids, Michigan, 2022)
"A Christian sociologist explains how the problem of the stranger lies at the root of many problems humanity faces, such as racism, sexism, and nationalism, but that an identity in Christ frees us to love strangers as neighbors and friends"--
Includes bibliographical references and index.
Keywords: Strangers -- Religious aspects -- Christianity; Identity (Psychology) -- Religious aspects -- Christianity